Does General and Specific Traits of Personality Predict Students' Academic Performance? - Jaber, Mohamed; Al-Samarrai, Basim; Salah, Afraa; Varma, Sudhir Rama; Karobari, Mohmed Isaqali; Marya, Anand (BioMed Research International, 2022)
Background and Objectives. This study examines whether personality profiles, personality factors, or clusters of personality factors are associated with academic success. Methods. The study includes all fifth-year dental students registered at the College of Dentistry, Ajman University, in 2019/2020. One hundred and seventy students were invited to complete personality and performance measures using the Big Five Inventory (BFI) scale; the weighted grade point average (GPA) was used to assess students' academic performance. Results. Of the 170 participants, 60% were female and 40% were male. Participants ranged in age from twenty-four to twenty-seven years, with an average age of twenty-four years. There was a relationship between personality scores obtained for the students and their subsequent academic performance. The broad conscientiousness, competence, achievement, and dutifulness predicted academic and clinical success. The prediction accuracy of conscientiousness was improved by the inclusion of dutifulness, self-discipline, and deliberation. Conclusion. This study confirms that the students' personality profile is a substantial predictor of academic performance and likely to help select future intakes of students, although a prospective study would be required for a definite answer to this question.